A REF6-dependent H3K27me3-depleted state facilitates gene activation during germination in Arabidopsis. (March 2023) - Pan, Jie; Zhang, Huairen; Zhan, Zhenping; Zhao, Ting; Jiang, Danhua
Abstract: Seed germination is a critical developmental switch from a quiescent state to active growth, which involves extensive changes in metabolism, gene expression, and cellular identity. However, our understanding of epigenetic and transcriptional reprogramming during this process is limited. The histone H3 lysine 27 trimethylation (H3K27me3) plays a key role in regulating gene repression and cell fate specification. Here, we profile H3K27me3 dynamics and dissect the function of H3K27 demethylation during germination in Arabidopsis. Our temporal genome-wide profiling of H3K27me3 and transcription reveals delayed H3K27me3 reprogramming compared with transcriptomic changes during germination, with H3K27me3 changes mainly occurring when the embryo is entering into vegetative development. RELATIVE OF EARLY FLOWERING 6 (REF6)-mediated H3K27 demethylation is necessary for robust germination but does not significantly contribute to H3K27me3 dynamics during germination, but rather stably establishes an H3K27me3-depleted state that facilitates the activation of hormone-related and expansin-coding genes important for germination. We also show that the REF6 chromatin occupancy is gradually established during germination to counteract increased Polycomb repressive complex 2 (PRC2). Our study provides key insights into the H3K27me3 dynamics during germination and suggests the function of H3K27me3 in facilitating cell fate switch. Furthermore, we reveal the importance of H3K27 demethylation-established transcriptional competence in gene activation during germination and likely other developmental processes.